2021
DOI: 10.3390/molecules26030589
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of New Demulsifiers Employing the Waste Polyethylene Terephthalate and their Demulsification Efficiency for Heavy Crude Oil Emulsions

Abstract: Two novel amphiphilic polyethylene amine terephthalate have been prepared via the glycolsis of polyethylene terephthalate (PET). The product, bis (2-hydroxyethyl terephthalate) (BHET), was converted to the corresponding dialkyl halide, bis(2-chloroethyl) terephthalate (BCET), using thionyl chloride (TC). This dialkyl compound was used for alkylation of dodecyl amine (DOA) and tetraethylenepentamine (TEPA) or pentaethylenehexamine (PEHA) to form the corresponding polyethylene amine terephthalate, i.e., DOAT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Further, TTB-AA showed a higher ability to reduce IFT than HTB-AA. The increased length of TTB-AA alkyl chains might explain their higher performance than HTB-AA …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, TTB-AA showed a higher ability to reduce IFT than HTB-AA. The increased length of TTB-AA alkyl chains might explain their higher performance than HTB-AA …”
Section: Resultsmentioning
confidence: 99%
“…Various studies have reported the use of AILs for the demulsification of crude oil emulsions. In our earlier work, we succeeded in synthesizing AILs and applying them to demulsify crude oil emulsions. ,,,, Herein, two novel AILs were synthesized and employed to demulsify water-in-oil (W/O) emulsions. 4-Tetradecylaniline (TA) and 4-hexylamine (HA) were reacted with tetrethylene glycol (TEG) in the presence of bis­(2-chloroethoxyethyl)­ether (BE) as a cross-linker, yielding corresponding ethoxylated amines TTB and HTB.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Different PET-based amphiphilic compounds were prepared and employed in our earlier works to demulsify heavy crude oil emulsions. 9–11…”
Section: Introductionmentioning
confidence: 99%
“…Much research was conducted to reveal the required conditions to coalesce and effectively improve dewatering efficiency [ 10 , 11 , 12 , 13 , 14 , 15 ]. An electric field with a strength smaller than the critical value could impact the coalescence and could increase the coalescing speed of the droplets.…”
Section: Introductionmentioning
confidence: 99%